2008
DOI: 10.1002/glia.20633
|View full text |Cite
|
Sign up to set email alerts
|

Kir4.1 and AQP4 associate with Dp71‐ and utrophin‐DAPs complexes in specific and defined microdomains of Müller retinal glial cell membrane

Abstract: The dystrophin-associated proteins (DAPs) complex consisting of dystroglycan, syntrophin, dystrobrevin, and sarcoglycans in muscle cells is associated either with dystrophin or its homolog utrophin. In rat retina, a similar complex was found associated with dystrophin-Dp71 that serves as an anchor for the inwardly rectifying potassium channel Kir4.1 and the aqueous pore, aquaporin-4 (AQP4). Here, using immunofluorescence imaging of isolated retinal Müller glial cells and co-immunoprecipitation experiments perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
87
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 35 publications
6
87
0
5
Order By: Relevance
“…54 Moreover, we have observed that even if AQP4 and Kir 4.1 reduced their protein content, they maintained a polarized expression on the perivascular glial endfeet, suggesting that a similar molecular mechanism is involved in membrane clustering for both proteins. Otherwise, in the retina of Dp71-null mice, AQP4 expression was reduced, whereas Kir 4.1 expression was unaffected, 11 and the deletion of a-syntrophin gene caused AQP4 reduction of AQP4 in Muller cells, but not of Kir 4.1. 55 These discrepancies could be explained by the fact that, in the mdx brain, 427 full-length dystrophin alone was completely lost, whereas the other isoforms, including Dp71 and syntrophin, were decreased, but preserved their link with AQP4 and Kir 4.1.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…54 Moreover, we have observed that even if AQP4 and Kir 4.1 reduced their protein content, they maintained a polarized expression on the perivascular glial endfeet, suggesting that a similar molecular mechanism is involved in membrane clustering for both proteins. Otherwise, in the retina of Dp71-null mice, AQP4 expression was reduced, whereas Kir 4.1 expression was unaffected, 11 and the deletion of a-syntrophin gene caused AQP4 reduction of AQP4 in Muller cells, but not of Kir 4.1. 55 These discrepancies could be explained by the fact that, in the mdx brain, 427 full-length dystrophin alone was completely lost, whereas the other isoforms, including Dp71 and syntrophin, were decreased, but preserved their link with AQP4 and Kir 4.1.…”
Section: Discussionmentioning
confidence: 93%
“…They express in a polarized way, on their perivascular endfeet, carrier membranes and channel proteins, including aquaporin-4 (AQP4) water channel and potassium channel Kir 4.1, which are responsible for the water flow rate and spatial K þ buffering control. [4][5][6][7][8][9] In the retina, AQP4 colocalizes with Kir 4.1, [9][10][11] suggesting a tight cooperation between the water flux and K þ siphoning generated by neuronal activity at the BBB interfaces. Moreover, AQP4 and Kir 4.1 rearrangement has been described in BBB alterations, coupled with cytotoxic edema and K þ -delayed buffering capacity.…”
mentioning
confidence: 99%
“…Although such a distribution is functionally important in potassium ion and water homeostasis, the mechanisms regulating the formation of these Kir4.1-and AQP4-enriched domains remain to be elucidated. AQP4 is associated with lipid raft-containing fractions in both brain and retina (27,35) as is another aquaporin, AQP5, that participates in fluid secretion in parotid gland cells (36). We therefore undertook a study to evaluate the role of lipid rafts in laminin-DG-dependent AQP4 clustering, and our data show that laminin induced a dramatic redistribution of GM1 into large cell surface clusters or macrodomains that colocalized extensively with ␤-DG and AQP4.…”
Section: Discussionmentioning
confidence: 98%
“…The cellular processes HSF1 regulates in cancer including energy metabolism, cell cycle signaling, DNA repair, apoptosis, cell adhesion, and extracellular matrix (Marc et al 2012). As the most ubiquitously expressed isoforms of dystrophin, Dp71 participates in various cellular processes, including cell adhesion, water homeostasis, and cell division in PC12 cells (Fort et al 2008;Acosta et al 2004). Compelling evidence supporting Dp71 and DAPC components in the nucleus suggests its possible biological function via the continuous network linking the plasma membrane to the nuclear envelope (Villarreal-Silva et al 2011).…”
Section: Discussionmentioning
confidence: 99%